2007
DOI: 10.1016/j.jcta.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

r-Qsym is free over Sym

Abstract: Our main result is a proof of the Florent Hivert conjecture [F. Hivert, Local action of the symmetric group and generalizations of quasi-symmetric functions, in preparation] that the algebras of r-Quasi-Symmetric polynomials in x 1 , x 2 , . . . , x n are free modules over the ring of Symmetric polynomials. The proof rests on a theorem that reduces a wide variety of freeness results to the establishment of a single dimension bound. We are thus able to derive the Etingof-Ginzburg [P. Etingof, V. Ginzburg, On m-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Diaconis et al (1992) showed that, when S = {1}, A {1} generates an n-dimensional commutative semisimple subalgebra of the group algebra, A(S n ) and A {1} has the same spectral decomposition as the transition matrix for top to random shuffles. Garsia and Wallach (2007) also proved the same result. Aldous and Diaconis (1986), Diaconis et al (1992) and recently Stark (2002) proved that n log n + cn top to random shuffles is sufficient for the deck to be random.…”
Section: Introductionsupporting
confidence: 64%
“…Diaconis et al (1992) showed that, when S = {1}, A {1} generates an n-dimensional commutative semisimple subalgebra of the group algebra, A(S n ) and A {1} has the same spectral decomposition as the transition matrix for top to random shuffles. Garsia and Wallach (2007) also proved the same result. Aldous and Diaconis (1986), Diaconis et al (1992) and recently Stark (2002) proved that n log n + cn top to random shuffles is sufficient for the deck to be random.…”
Section: Introductionsupporting
confidence: 64%
“…This problem is also an ingredient of the proof of Hivert's conjecture by Garsia and Wallach [16]. It can be solved in many different ways.…”
Section: 2mentioning
confidence: 99%
“…The Hopf algebra of r-quasisymmetric functions is defined in [15] by Hivert. In [10], Garsia and Wallach showed that the algebra of r-quasisymmetric functions is free over symmetric functions. In the last section, we introduce the Hopf algebra of rquasisymmetric functions in noncommuting variables.…”
Section: Introductionmentioning
confidence: 99%